Interpretation of Building Maintenance Factors on Employee Convenience at The Factory of PT Campina Ice Cream Industry Tbk - Setiawan, Rudi; Durrotun Nasihien, Ronny; Sutapa, I Ketut; Irwansyah, Defi (Malikussaleh University, Aceh, Indonesia, 2024)
Buildings are an essential part of human life. Building maintenance is carried out to provide security and comfort for building users. This study aims to determine and analyze the implementation of building maintenance, the influence of maintenance factors on building maintenance, and what maintenance factors have a dominant influence on the comfort of building users at PT. Campina Ice Cream Industry Tbk. This study uses a quantitative approach to data collection using a questionnaire. The population used in this study were employees at the PT. Campina Ice Cream Industry Tbk has a total of 520 employees. Meanwhile, the research sample was 72 employees at PT. Campina Ice Cream Industry Tbk. The data was tested using the validity test and reliability test. The analytical method used is multiple linear regression analysis with hypothesis testing using the t-test. The study results show that the condition of building maintenance is carried out at the factory of PT. Campina Ice Cream Industry Tbk, through architectural, mechanical, and electrical maintenance, has been carried out well, starting from wall and window maintenance and wall/glass cleaning, properly providing and maintaining health facilities, and holding office facilities and infrastructure, especially in regular electrical installations. The results of the t-test show that architectural, mechanical, and electrical maintenance has a significant effect on comfort. The building maintenance variable that has the dominant influence on comfort is the electrical maintenance variable.